A method for preparing a wear-resistant composite material
By combining modified filler and polytetrafluoroethylene, a polytetrafluoroethylene composite material with higher wear resistance and tensile strength was prepared, solving the problem of insufficient performance of existing materials.
Patent Information
- Application Number
- CN202410195843.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-02-22
AI Technical Summary
The wear resistance and tensile strength of existing polytetrafluoroethylene materials are insufficient, making it difficult to meet the needs of higher performance.
Modified fillers are prepared by mixed calcination of fullerene fluoride, nanosilicon carbide, nanoboronitride, nanoalumina and polyvinyl alcohol, and mixed with polyether ether ketone, silane coupling agent, polydimethylsiloxane and polytetrafluoroethylene. After drying, pressing molding and sintering, wear-resistant composite materials are prepared.
The prepared wear-resistant composite material has lower coefficient of friction and higher tensile strength, which significantly improves the wear resistance and performance of the material.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a preparation method of a wear-resistant composite material. Background Art
[0002] Polytetrafluoroethylene (PTFE) is a commonly used plastic with good corrosion resistance and certain lubricity. It is widely used in various mechanical equipment to play a sealing role. That is, polytetrafluoroethylene is often used as a sealing material.
[0003] In order to improve the application performance of polytetrafluoroethylene in the prior art, copper powder or reinforcing materials are usually added to improve the wear resistance and tensile strength of polytetrafluoroethylene. However, the friction coefficient of the polytetrafluoroethylene material obtained by this improved method is generally difficult to be lower than 0.15, and the wear resistance needs to be further improved. And the tensile strength of the prepared polytetrafluoroethylene material is often below 31MPa.
[0004] Therefore, it is necessary to provide a new preparation method to prepare polytetrafluoroethylene materials with better wear resistance and tensile strength. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. The present invention provides a method for preparing a wear-resistant composite material. The wear-resistant composite material prepared by the preparation method of the present invention is a polytetrafluoroethylene material, which has good wear resistance and further has high tensile strength.
[0006] The invention utilizes fullerene fluoride, nano silicon carbide, nano boron nitride, nano aluminum oxide and polyvinyl alcohol for mixed calcination (the process allows each component to be evenly dispersed, and the polyvinyl alcohol helps to improve the compatibility of each component during the calcination temperature rise process, and the polyvinyl alcohol is decomposed during calcination) to obtain a modified filler, and then the modified filler is mixed with polyetheretherketone, silane coupling agent, polydimethylsiloxane, water and polytetrafluoroethylene, and the silane coupling agent is hydrolyzed to improve the dispersion uniformity of the modified filler and the polyetheretherketone, polydimethylsiloxane and polytetrafluoroethylene. The obtained mixed material is dried, pressed and sintered to finally obtain a wear-resistant composite material, and the composite material also has good tensile strength.
[0007] The present invention provides a method for preparing a wear-resistant composite material, comprising the following steps:
[0008] Stirring and mixing polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane and water to obtain a mixed material;
[0009] The mixed material is dried, then pressed and sintered to obtain the wear-resistant composite material;
[0010] The preparation process of the modified filler comprises the following steps: taking fullerene fluoride, nano silicon carbide, nano boron nitride, nano aluminum oxide and polyvinyl alcohol, stirring and mixing them, calcining them in an oxygen-containing atmosphere, and crushing them to obtain the modified filler.
[0011] Preferably, the mass ratio of polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane, and water is 80: (2-10): (1-8): (5-15): (5-20); further preferably, the mass ratio of polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane, and water is 80: (3-8): (1.5-6.5): (5-12): (5-20). The selection of specific dosage is conducive to obtaining a material with better wear resistance.
[0012] Preferably, the mass ratio of fullerene fluoride, nano-silicon carbide, nano-boron nitride, nano-aluminum oxide and polyvinyl alcohol is 0.1:(0.2-1):(0.3-1.2):(0.3-1.2):(0.5-3); further preferably, the mass ratio of fullerene fluoride, nano-silicon carbide, nano-boron nitride, nano-aluminum oxide and polyvinyl alcohol is 0.1:(0.2-0.8):(0.3-1.0):(0.3-1.0):(0.5-2.5).
[0013] Preferably, during the preparation of the modified filler, the calcination temperature is 800-950° C. and the calcination time is 1-2 hours.
[0014] Preferably, during the calcination process, the temperature is increased at a rate of 8-12°C to 800-950°C.
[0015] Preferably, the fullerene fluoride comprises C 60 (CF3)6 or C 60 (CF3) 10 .
[0016] Preferably, the drying temperature is 90-100° C., and the drying time is 1-3 hours.
[0017] Preferably, the pressing pressure is 50-55 MPa, and the pressing time is 20-50 minutes.
[0018] Preferably, the sintering temperature is 340-360° C., and the sintering time is 1-3 hours.
[0019] Preferably, during the sintering process, the temperature is increased at a rate of 5-10°C.
[0020] Preferably, a method for preparing a wear-resistant composite material comprises the following steps:
[0021] Stirring and mixing polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane and water to obtain a mixed material;
[0022] The mass ratio of the polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane and water is 80:(2-10):(1-8):(5-15):(5-20);
[0023] The mixed material is dried at a temperature of 90-100° C. for a drying time of 1-3 hours, and then pressed at a pressure of 50-55 MPa for a pressing time of 20-50 minutes, and sintered at a temperature of 340-360° C. During the sintering process, the temperature is increased at a rate of 5-10° C. for a sintering time of 1-3 hours to obtain the wear-resistant composite material;
[0024] The preparation process of the modified filler comprises the following steps: taking fullerene fluoride, nano silicon carbide, nano boron nitride, nano aluminum oxide and polyvinyl alcohol, stirring and mixing them, wherein the mass ratio of the fullerene fluoride, nano silicon carbide, nano boron nitride, nano aluminum oxide and polyvinyl alcohol is 0.1:(0.2-1):(0.3-1.2):(0.3-1.2):(0.5-3), calcining them in an oxygen-containing atmosphere (such as air), heating them at a rate of 8-12° C. to 800-950° C., calcining them for 1-2 hours, and crushing them to obtain the modified filler.
[0025] Preferably, polyphenylene sulfide is also added during the preparation of the mixed material. The addition of polyphenylene sulfide helps to further improve the wear resistance of the wear-resistant composite material.
[0026] Preferably, the mass ratio of polyphenylene sulfide to polytetrafluoroethylene is (1-5):80.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0028] (1) The present invention utilizes fullerene fluoride, nano silicon carbide, nano boron nitride, nano aluminum oxide, and polyvinyl alcohol for mixed calcination (this process allows each component to be uniformly dispersed, and polyvinyl alcohol helps to improve the compatibility of each component during the calcination temperature rise process. During calcination, polyvinyl alcohol decomposes, and the use of fullerene fluoride is conducive to better compatibility with polytetrafluoroethylene) to obtain a modified filler, and then the modified filler is mixed with polyetheretherketone, silane coupling agent, polydimethylsiloxane, water, and polytetrafluoroethylene. The silane coupling agent is hydrolyzed to improve the dispersion uniformity of the modified filler and polyetheretherketone, polydimethylsiloxane, and polytetrafluoroethylene. The obtained mixed material is dried, pressed, and sintered to finally obtain a wear-resistant composite material. The wear-resistant composite material has a small friction coefficient, for example, a friction coefficient not exceeding 0.12, and the composite material also has good tensile strength.
[0029] (2) The addition of polyphenylene sulfide helps to further improve the wear resistance of the wear-resistant composite material. DETAILED DESCRIPTION
[0030] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0031] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0032] Example 1
[0033] A method for preparing a wear-resistant composite material comprises the following steps:
[0034] Stirring polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane and water at a speed of 300 rpm for 30 minutes to obtain a mixed material; the mass ratio of polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane and water is 80:3:4:6:15;
[0035] The mixed material is dried at a temperature of 95°C for 2 hours, and then pressed at a pressure of 52MPa for 40 minutes, and sintered at a temperature of 350°C. During the sintering process, the temperature is increased to 350°C at a rate of 8°C, and sintered at 350°C for 3 hours to obtain a wear-resistant composite material;
[0036] The preparation process of the modified filler comprises the following steps: taking fullerene fluoride C 60(CF3)6, nano silicon carbide, nano boron nitride, nano alumina and polyvinyl alcohol are stirred and mixed. The mass ratio of fullerene fluoride, nano silicon carbide, nano boron nitride, nano alumina and polyvinyl alcohol is 0.1:0.3:0.5:0.6:1.5. The mixture is calcined in an oxygen-containing atmosphere (such as air). The temperature is increased at a rate of 10°C to 850°C. The mixture is calcined at 850°C for 1 hour and crushed to obtain a modified filler with a mesh size of 150-200.
[0037] Example 2
[0038] A method for preparing a wear-resistant composite material comprises the following steps:
[0039] Stirring polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane and water at a speed of 400 rpm for 30 minutes to obtain a mixed material; the mass ratio of polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane and water is 80:8:6:5:18;
[0040] The mixed material is dried at a temperature of 100° C. for 1 hour, and then pressed at a pressure of 55 MPa for 30 minutes, and sintered at a temperature of 355° C. During the sintering process, the temperature is increased to 355° C. at a rate of 8° C., and sintered at 355° C. for 3 hours to obtain a wear-resistant composite material;
[0041] The preparation process of the modified filler comprises the following steps: taking fullerene fluoride C 60 (CF3) 10 , nano silicon carbide, nano boron nitride, nano alumina, and polyvinyl alcohol are stirred and mixed, the mass ratio of fullerene fluoride, nano silicon carbide, nano boron nitride, nano alumina, and polyvinyl alcohol is 0.1:0.4:0.8:0.8:1.8, and calcined in an oxygen-containing atmosphere (such as air), and the temperature is increased at a rate of 10°C to 900°C, calcined at 900°C for 1 hour, and crushed to obtain a modified filler with a mesh size of 150-200 mesh.
[0042] Example 3
[0043] A method for preparing a wear-resistant composite material comprises the following steps:
[0044] Stirring polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane, water and polyphenylene sulfide at a speed of 300 rpm for 30 minutes to obtain a mixed material; the mass ratio of polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane, water and polyphenylene sulfide is 80:3:4:6:15:1.5;
[0045] The mixed material is dried at a temperature of 95°C for 2 hours, and then pressed at a pressure of 52MPa for 40 minutes, and sintered at a temperature of 350°C. During the sintering process, the temperature is increased to 350°C at a rate of 8°C, and sintered at 350°C for 3 hours to obtain a wear-resistant composite material;
[0046] The preparation process of the modified filler comprises the following steps: taking fullerene fluoride C 60 (CF3)6, nano silicon carbide, nano boron nitride, nano alumina and polyvinyl alcohol are stirred and mixed. The mass ratio of fullerene fluoride, nano silicon carbide, nano boron nitride, nano alumina and polyvinyl alcohol is 0.1:0.3:0.5:0.6:1.5. The mixture is calcined in an oxygen-containing atmosphere (such as air). The temperature is increased at a rate of 10°C to 850°C. The mixture is calcined at 850°C for 1 hour and crushed to obtain a modified filler with a mesh size of 150-200.
[0047] Comparative Example 1
[0048] Compared with Example 1, in Comparative Example 1, an equal amount of C 60 Substituting the fullerene fluoride C in Example 1 60 (CF3)6, the rest of the process is the same as in Example 1.
[0049] Comparative Example 2
[0050] Compared with Example 1, in Comparative Example 2, an equal amount of copper powder is used to replace the nano-alumina in Example 1, and the rest of the process is the same as that of Example 1.
[0051] Comparative Example 3
[0052] Compared with Example 1, in Comparative Example 3, an equal amount of nano-ferrosoferric oxide is used to replace the nano-aluminum oxide in Example 1, and the rest of the process is the same as that in Example 1.
[0053] Comparative Example 4
[0054] Compared with Example 1, the difference of Comparative Example 4 is that the fullerene fluoride C is not 60 (CF3) 10 , nano silicon carbide, nano boron nitride, nano alumina, and polyvinyl alcohol are not calcined but directly mixed, and the rest of the process is the same as in Example 1.
[0055] Product effect testing
[0056] 1. Wear resistance test
[0057] The wear-resistant composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for friction coefficient and wear volume under the friction and wear conditions of a load of 30 N, a rotation speed of 900 rpm, dry friction for 1 hour, and a grinding ball of GCr15 steel. The results are shown in Table 1.
[0058] Table 1
[0059] Friction coefficient <![CDATA[Wear volume (mm 3 )]]> Example 1 0.12 0.18 Example 2 0.11 0.16 Example 3 0.10 0.13 Comparative Example 1 0.16 0.32 Comparative Example 2 0.20 0.49 Comparative Example 3 0.24 0.61
[0060] It can be seen from Table 1 that the wear-resistant composite materials prepared in Examples 1-3 of the present invention have lower friction coefficients and smaller wear volumes than those in Comparative Examples 1-3, indicating that the wear-resistant composite materials prepared in the present invention have better wear resistance.
[0061] It can be seen from Comparative Example 1 and Example 1 that the use of fullerene fluoride C 60 (CF3)6, relative to C 60 In terms of compatibility with other components of the system, the reason may be that both fullerene fluoride and polytetrafluoroethylene contain fluorine, and the dispersibility is improved, thereby improving the wear resistance of the wear-resistant composite material.
[0062] It can be seen from Comparative Examples 2-3 and Example 1 that the nano-alumina of the present invention should not be replaced by other metals or metal oxides, indicating that the components in the modified filler of the present invention are selective.
[0063] 2. Tensile strength test
[0064] The wear-resistant composite materials prepared in Example 1 and Comparative Example 4 were subjected to a tensile strength test. The test standard was carried out with reference to GB / T1040.2-2006. A 1A type specimen was used during the test, the specimen gauge length was 50.0±0.5 mm, and a universal testing machine was used for the test. The tensile rate was 50 mm / min, 5 specimens were tested, and the average tensile strength of the 5 specimens was taken. The results are shown in Table 2.
[0065] Table 2
[0066] Tensile strength(MPa) Example 1 35.8 Comparative Example 4 30.1
[0067] It can be seen from Table 2 that the wear-resistant composite material prepared in Example 1 of the present invention has a stronger tensile strength than that of Comparative Example 1. It can be seen that the modification process of the filler in the present invention is helpful to improve the tensile strength of the wear-resistant composite material.
[0068] The above content describes the basic principle and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that protection scope of the present invention is not limited by the above-described embodiments. Without departing from the spirit and scope of the present invention, the present invention also has various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed for protection.
Claims
1. A method for preparing a wear-resistant composite material, characterized in that: The following steps are involved: Stirring and mixing polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane and water to obtain a mixed material; The mixed material is dried, then pressed and sintered to obtain the wear-resistant composite material; The preparation process of the modified filler comprises the following steps: taking fullerene fluoride, nano silicon carbide, nano boron nitride, nano aluminum oxide and polyvinyl alcohol, stirring and mixing them, calcining them in an oxygen-containing atmosphere, and crushing them to obtain the modified filler.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the polytetrafluoroethylene, modified filler, polyetheretherketone, silane coupling agent, polydimethylsiloxane and water is 80:(2-10):(1-8):(5-15):(5-20).
3. The preparation method according to claim 1, characterized in that: The mass ratio of the fullerene fluoride, nano silicon carbide, nano boron nitride, nano aluminum oxide and polyvinyl alcohol is 0.1: (0.2-1): (0.3-1.2): (0.3-1.2): (0.5-3).
4. The preparation method according to claim 1, characterized in that: During the preparation of the modified filler, the calcination temperature is 800-950° C. and the calcination time is 1-2 hours.
5. The preparation method according to claim 1, characterized in that: The fullerene fluoride comprises C 60 (CF3)6 or C 60 (CF3) 10 .
6. The preparation method according to claim 1, characterized in that: The pressure of the pressing molding is 50-55 MPa, and the time of the pressing molding is 20-50 minutes.
7. The preparation method according to claim 1, characterized in that: The sintering temperature is 340-360° C., and the sintering time is 1-3 hours.
8. The preparation method according to claim 1, characterized in that: The drying temperature is 90-100° C., and the drying time is 1-3 hours.
9. The preparation method according to claim 1, characterized in that: In the process of preparing the mixed material, polyphenylene sulfide is also added.
10. The preparation method according to claim 9, characterized in that: The mass ratio of the polyphenylene sulfide to polytetrafluoroethylene is (1-5):80.
Citation Information
Patent Citations
Composite abrasion-resisting and high-temperature-resisting high-temperature conveying belt
CN105730980A
Wear-resistant PEEK composite material
CN112812497A